Side Differences Regarding the Limb Symmetry Index in Healthy Professional Athletes - Lambert, Christophe; Pfeiffer, Thomas; Lambert, Maxime; Brozat, Benedikt; Lachmann, Daniel; Shafizadeh, Sven; Akoto, Ralph (International Journal of Sports Medicine, 2020)
Side differences in the limb symmetry index during hop tests have been rarely investigated in uninjured athletes. Unknown differences can result in false interpretation of hop tests and affect return to sport decision. Hypothesis was that un-injured athletes in Judo and Taekwondo have side differences in hop test and that asymmetries can be predicted based on the athletes fighting display. Differences, risk relationships were analyzed using the chi-squared test and the odds ratio. A two-tailed p value of<0.05 was considered statistically significant. 115 athletes from the national teams were included (mean age 18.4 years; range 13–27 years). 93, 97.4 and 98.3% did not have symmetric hop distance for three hop tests. Up to a quarter did not reach a limb symmetry index of>90. Moreover, 57.4% (n=66) reached longer jumping distance with the standing leg. Ignoring such pre-existent side differences in evaluation of hop tests and not knowing which limb was dominant prior the injury, can lead to premature or delayed return to sports in the rehabilitation process. Therefore, it might be helpful to refer to individual jump lengths for each limb in case of injury by using hop tests in pre-season screening in professional athletes in Judo and Taekwondo.
Keywords: hop test; RTP; ACLR